2021
DOI: 10.1002/onco.13728
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Myxofibrosarcoma with Durable Response to Temozolomide Followed by Atezolizumab: A Case Report

Abstract: Myxofibrosarcoma (MFS) is a well‐recognized histotype of soft tissue sarcomas that generally presents with localized disease. Herein, we describe the case of a patient with metastatic MFS who experienced durable response to sixth‐line therapy with temozolomide. Upon further progression, his tumor was notable for a high tumor mutational burden, and he was subsequently treated with seventh‐line immunotherapy, atezolizumab, achieving a second durable response. This case highlights the role of immunotherapy after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Yu et al [ 137 ] reported a major response to pembrolizumab in an adult patient with an undifferentiated embryonal sarcoma of the liver. In metastatic myxofibrosarcoma, partial responses have been reported with pembrolizumab [ 138 ] and atezolizumab plus temozolomide [ 139 ]. These data, together with the data from AcSé trial, suggest that ICIs may be useful for certain subtypes of rare sarcoma, especially when selected by immune biomarkers such as the PDL1 expression.…”
Section: Immunotherapy For Sarcoma: Clinical Resultsmentioning
confidence: 99%
“…Yu et al [ 137 ] reported a major response to pembrolizumab in an adult patient with an undifferentiated embryonal sarcoma of the liver. In metastatic myxofibrosarcoma, partial responses have been reported with pembrolizumab [ 138 ] and atezolizumab plus temozolomide [ 139 ]. These data, together with the data from AcSé trial, suggest that ICIs may be useful for certain subtypes of rare sarcoma, especially when selected by immune biomarkers such as the PDL1 expression.…”
Section: Immunotherapy For Sarcoma: Clinical Resultsmentioning
confidence: 99%
“…A twosided p-value < 0.05 was considered statistically significant. Statistical analyses were performed using SPSS 28.0 and SAS 9.4. patients had received a median RT dose for the IT of 57 Gy (45-66), in a median of 30 fractions (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Roughly 62% developed OST in the head and neck (n = 10) (p ⩽ 0.001), and most had high-grade tumours (93%, n = 13/14).…”
Section: Discussionmentioning
confidence: 99%
“…Myxofibrosarcoma (MFS) expresses high levels of immune microenvironment markers, and some case reports support PD-1 inhibition in myxofibrosarcoma, which is further explored in a Phase II trial (ENVASARC, NCT04480502) (20)(21)(22)(23).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%